Risk factors associated with shoulder pain and disability across the lifespan of competitive swimmers - Tate, A.; Turner, G. N.; Knab, S. E.; Jorgensen, C.; Strittmatter, A.; Michener, L. A. (Journal of Athletic Training, 2012)
Abstract: Context: The prevalence of shoulder pain among competitive swimmers is high, but no guidelines exist to reduce shoulder injuries. Elucidating differences between swimmers with and without shoulder pain can serve as a basis for the development of a program to prevent shoulder injury that might lead to pain and dysfunction. Objective: To determine whether physical characteristics, exposure, or training variables differ between swimmers with and without shoulder pain or disability. Design: Cross-sectional study. Setting: Multisite swimming centers. Patients or Other Participants: A total of 236 competitive female swimmers aged 8 to 77 years. Data Collection and Analysis: Participants completed the Penn Shoulder Score and underwent testing of core endurance, range of motion, muscle force production, and pectoralis minor muscle length and the Scapular Dyskinesis Test. Swimmers were grouped by age for analysis: ages 8 to 11 years (n = 42), 12 to 14 years (n = 43), 15 to 19 years (high school, n = 84), and 23 to 77 years (masters, n = 67). Comparisons were made between groups with and without pain and disability using independent t tests for continuous data and ?2 analyses and Fisher exact tests for categorical data. Results: Nine (21.4%) swimmers aged 8 to 11 years, 8 (18.6%) swimmers aged 12 to 14 years, 19 (22.6%) high school swimmers, and 13 (19.4%) masters swimmers had shoulder pain and disability. Differences that were found in 2 or more age groups between athletes with and without shoulder pain and disability included greater swimming exposure, a higher incidence of previous traumatic injury and patient-rated shoulder instability, and reduced participation in another sport in the symptomatic groups (P < .05). Reduced shoulder flexion motion, weakness of the middle trapezius and internal rotation, shorter pectoralis minor and latissimus, participation in water polo, and decreased core endurance were found in symptomatic females in single varying age groups (P < .05). Conclusions: Female competitive swimmers have shoulder pain and disability throughout their lives. Given that exposure and physical examination findings varied between athletes with and without substantial pain and disability, a program to prevent shoulder injury that might lead to pain and dysfunction appears warranted and might include exposure reduction, cross-training, pectoral and posterior shoulder stretching, strengthening, and core endurance training.